Odpowiedzi

Najlepsza Odpowiedź!
2009-10-27T19:27:36+01:00
A)
m-(m²-2m+1}-(m²-1) = 0
m-m²+2m-1-m²+1 = 0
-2m²+3m = 0
Δ =3²-4*(-2)*0 =9
x₁ = -3-3/(-4) =3/2
x₂ =-3+3/(-4) =0/-4 =0


c)
(3x-1)*(2x+3) = (x+5)*6x
6x²+9x-2x-3 = 6x²+30x
-23x = 3
x = -3/23
2009-10-27T19:32:25+01:00
A) m-(m-1)²=(m+1)(m-1)
m-(m²-2m+1)=m²-1
m-m²+2m-1=m²-1
3m-2m₂=0
m=o
b)3x-1przez2-x+4przez3>5x-11przez4/×12
6(3x-1)-4(x+4)>3(5x-11)
18x-6-4x-16>15x-33
-x=-11/÷(-1)
x<11
c)3x-1przezx+5=6xprzez 2x+3
(3x-1)(2x+3)=6x(x+5)
6x²+9x-2x-3=6x²+30x
-23x=3/÷(-23)
x=-3/23
Prosze:))